A review of the development on AoFei animation film derivatives - Ma, Yueshi; Mohd Zawawi, Julia Wirza; Mohamad, Zulkifli; Wang, Zijun; Ruan, Qijie (Human Resource Management Academic Research Society (HRMAS), 2023)
With the development of the new media and mass communication, the animation industry in China has undergone tremendous changes in tandem. These changes are reflected in the increasing number of original animation works, the quality of animation production and its cultural heritage, and the fact that the audience is no longer limited to children and teenagers.As a new force in the development of China's animation industry, the dissemination of animation film derivatives provides a platform for audiences to support their favourite animation films.Due to the maturity of the derivatives industry and the lack of awareness of the film industry in developing derivatives, the inability to plan derivatives in the planning and production of films and the single mode of communication, the overall communication of Chinese film derivatives to audiences is relatively lagging behind.This paper selects AoFei Entertainment, a leader in China's animation industry, and reviews the development of AoFei's animation film derivatives. On the one hand, it makes an analysis of the gap between the development of animation film derivatives in China and that of developed countries (USA and Japan). On the other hand, it aims to provide audiences who love animated films with a channel for the dissemination of derivatives using culture as a creative image.